The Implementation Of Inquiry-Based Learning In Teaching Writing To The Seventh Grade Student Of SMP Negeri 5 BoyolaliIn 2013/2014 Academic Year - Utari, Wahyu Ariyani, Aryati Prasetyarini, M.Pd, Drs. Djoko Srijono, M.Hum (2014)
The objectives of this research are: (1) to know the implementation of Inquiry-based Learning consisting the objectives of teaching writing, the materials, and the the procedure of the Inquiry-based Learning (2) to describe the problem faced by the teacher in teaching writing using the Inquiry-based Learning at the seventh grade student of SMP Negeri 5 Boyolali. The writer uses descriptive research. The subject of this descriptive research is the seventh grade students of SMP Negeri 5 Boyolali in 2013/2014 academic year. The writer gets the data of this research from event, informant, and document. The method of collecting data are observation and interview about teaching writing using Inquiry-based Learning. The result of the analysis show that (1) the implementation of Inquirybased Learning in teaching writing at the seventh grade of SMPN 5 Boyolali that is conducted into five inquiry cycle process in the 2013 curriculum such as observing, questioning, collecting information or experimenting, associating or information processing, and communicating. The implementation of Inquirybased Learning in teaching writing was totally full and appropriate with the Inquiry-based Learning. But in the second and fourth meeting, that were not totally full all of the inquiry cycle. It didn't pass the observing, questioning, collecting information or experimenting, associating or information processing stage. The teaching material is taken only from English book that was comprising such as definition, social function, generic structure, and grammar. Then the objective of teaching writing at the seventh grade student is to develop the student become more creative, and active in writing skill. And specifically in order the students can master in writing aspect: structure, spelling, punctuation, and vocabulary. 2) The problem faced by the teacher such as classroom management, limited time, strong students' dominance, lack of teaching media, and the appropriate teaching technique choice.